Aplicação de uma escala de avaliação da aprendizagem de ciência no campo - P. Ferreira (2010)
This paper presents the results of applying a rating scale of learning science in the field. These studies were developed in the ambit a PhD project in progress which seeks to emphasize the importance of using the field work in research and teaching of geology and, somehow, the connection between geological research and pedagogical intervention (didactic transposition ). The application of the scale resulted from the performance of six field trips, with 8 high school classes Biology / Geology, having been obtained from a sample of 171 inquiries